9th mathematics exercise question with answer, Mathematics

Multiplication of Polynomials – Exercise 3.1.5-Class 9

If a + b + c = 0, prove the following: (i) (b + c) (b – c) + a (a + 2b) = 0 Given a + b + c = 0 the a + b = -c, b + c = -a, c + a = -b we have L.H.S = (b +… Continue reading Multiplication of Polynomials – Exercise 3.1.5-Class 9

Advertisements
9th mathematics exercise question with answer, Mathematics

Multiplication of Polynomials Exercise 3.1.5-Class 9

If a + b + c = 0, prove the following: (i) (b + c) (b – c) + a (a + 2b) = 0 Given a + b + c = 0 the a + b = -c, b + c = -a, c + a = -b we have L.H.S = (b +… Continue reading Multiplication of Polynomials Exercise 3.1.5-Class 9